Pengaruh Pengawasan, Disiplin dan Motivasi Terhadap Kinerja Guru - Ahmad Rivai (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine the effect of supervision, discipline and motivation on teacher performance in public elementary schools in the Education Office of the UPT Medan Area, Medan City, either partially or simultaneously. The population in this study was limited to the teachers of SD Negeri in the UPT Education Office, Medan Area, Medan City, totaling 208 people. Approach is used to determine the sample. Given the large number of populations above, the researcher determines the number of samples using the Slovin formula. Thus the sample in this study was 68 public elementary school teachers in the UPT Education Office, Medan Area, Medan City. Data collection techniques in this study were questionnaires (Questioner) and interviews (interview). While the data analysis technique used is multiple regression. The results showed that partially, supervision, discipline and motivation had a positive and significant effect on the performance of teachers at the State Elementary School of the UPT Education Office, Medan Area, Medan City. Simultaneously, supervision, discipline and motivation have a positive and significant effect on the performance of teachers at the State Elementary School of the Education Office of the UPT District of Medan Area, Medan City